2020
DOI: 10.2460/ajvr.81.12.985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a simple continuous versus simple interrupted suture pattern for the repair of a large, open duodenal defect with a jejunal serosal patch in a canine cadaveric model

Abstract: OBJECTIVE To determine whether jejunal serosal patches could securely seal large, open defects in duodenal segments harvested from canine cadavers and to compare intraluminal pressures at which leakage first occurred and maximal intraluminal pressures for repaired duodenal segments between 2 suture patterns. SAMPLE Duodenal and jejunal segments from 9 canine cadavers. PROCEDURES 20 constructs were created through repair of large, open duodenal defects with circumferential suturing of an intact jejunal segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…The current study reported substantially higher ILPs in fresh and cooled feline intestine in comparison with previous reports of canine intestines 1,6 . This could be due to a slower rate of infusion used in this study (100 mL/h) in comparison with other studies reporting 999 mL/h 1,5,6,12,19 and 900 mL/h, 7,8 thereby allowing the intestine to distend at a lower rate before leakage, but time to leakage was not recorded. During the prestudy pilot testing, 999 mL/h was initially used but leakage occurred and obscured the enterotomy site quickly so that it was challenging to determine the location of leakage reliably.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…The current study reported substantially higher ILPs in fresh and cooled feline intestine in comparison with previous reports of canine intestines 1,6 . This could be due to a slower rate of infusion used in this study (100 mL/h) in comparison with other studies reporting 999 mL/h 1,5,6,12,19 and 900 mL/h, 7,8 thereby allowing the intestine to distend at a lower rate before leakage, but time to leakage was not recorded. During the prestudy pilot testing, 999 mL/h was initially used but leakage occurred and obscured the enterotomy site quickly so that it was challenging to determine the location of leakage reliably.…”
Section: Discussioncontrasting
confidence: 77%
“…Canine cadaveric studies involving the gastrointestinal tract have increased during the past 3 years (2020-2022) [1][2][3][4][5][6][7][8][9] after a novel study 7 was performed by Aeschlimann et al in 2018. This study compared leak testing in frozenthawed, cooled, and fresh porcine jejunal tissue due to its similarity to canine jejunal tissue in order to evaluate the type of tissue that may be more reliable in assessing enterotomy leak pressures. 7 As far as the authors of the current study are aware, it has not yet been established whether fresh or cooled feline cadaveric intestine is sufficient as an ex vivo model for feline intestinal surgery and species differences might exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation